Forecasting Of Greenhouse Gases and Air Quality Prediction Using Matlab Analytics - et. al., R. Sivaprasad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Examining and maintaining air quality is the most essential activity in many industrial and urban areas today. Air pollution is a serious danger, which influences both man’s health and ecosystem. It is the circumstance at which the presence of harmful substances in the aerosphere, due to various activities of mankind and nature like volcanoes eruptions, led to degrading effects on nation’s welfare and also the living ecosystem. Human activities are major air pollutants which includes combustion of fossil fuels, industrial activities like manufacturing, refining, mining etc. Amongst the air pollutants nitrogen oxides, sulphur oxides, carbon monoxides, ozone and organic compounds can volatilize and enter the atmos. According to the reports collected from the World Health organization, 2.4 million individuals die due to air pollution annually and out of these 1.5million from indoor air pollution. Consequently, there are more road accident deaths because of low visibility of roads resulting from poor air quality. There is an emerging need of a system to alert and also predict quality of air to avoid these mortal dangers.